DISEMINASI MORAL ACTING DALAM MEMBANGUN NILAI KARAKTER: Studi Kasus Siswa Mts Takhassus Al-Qur’an Bonang Demak - Zuhri, Zuhri; Faizah, Faizah (Jurnal Studi Islam dan Sosial, 2024)
The current behavior of students is very sad and worrying, not only students towards teachers but also towards each other, such as; bullying, fighting teachers, beatings. In fact, he has gained knowledge from teachers with noble behavior, through learning in the classroom and outside the classroom, but the impact has not been maximized, so he needs to take a step in building character values within himself through habituation in the madrasa which can grow the soul to internalize all the madrasa curriculum. This research aims to analyze learning and guidance as well as habituation (moral acting) that applies in madrasas, so that students have noble character as an implication of the education and skills process in madrasas, as well as institutionalizing the madrasa culture that has been built over a long time, and can be accepted by all school residents. This research uses a qualitative method, with a descriptive approach, namely the researcher analyzes the "habituation" method in madrasas and what forms of habituation there are, as well as noble moral values by adhering to theory and practice. The results of this research show that; Moral acting has become a culture at Madrasah Tsanawiyah Takhassus al-Qur'an with habits that have been established in the school, as well as regular assistance from teachers and transfer to other students, so that the school culture is the result of the creation of the school community (principal, teaching staff, students, homeroom teacher, committee, education staff) which are instilled through daily activities in accordance with the curriculum that has been determined and applied.